RESONANCE Registry: rationale and design of the retrospective and prospective longitudinal, observational registry in pediatric and adult patients with recurrent pericarditis. (14th October 2021) - Reid, A; Klein, A; Lin, D; Abbate, A; Luis, S A; Petersen, J; Portman, M; Winnowski, D; Malinowski, A; Marden, L; Paolini, J F; Martin, D
Abstract: Background: Annually in the United States (US), an estimated 80–90, 000 patients are diagnosed with acute pericarditis and 15–30% experience recurrent pericarditis (RP), resulting in increased morbidity and reduced health-related quality of life (HRQoL). Treatment options include non-steroidal anti-inflammatory drugs (NSAIDs) and colchicine. Corticosteroids (CS) are often added to the treatment plan in RP despite CS-associated adverse events and inherent potentiation of recurrence with long-term treatment. A recent Phase 3 clinical trial RHAPSODY (NCT03737110) demonstrated efficacy and safety of rilonacept, an interleukin-1 α and β cytokine trap, in patients with RP. RHAPSODY data helped support FDA approval of the first therapy for RP. With the emergence of this targeted therapy, there is increased interest to learn more about this disease with the goal to better inform treatment and management decisions and improve long-term outcomes. Purpose: RESONANCE Registry aims to evaluate the natural history of RP by collecting retrospective and prospective, longitudinal physician- and patient-reported outcomes data in real-world clinical practice across the US. Methods: RP patients with active disease (recurrence within 3 years) will have both retrospective and prospective data collected (Figure 1) for as long as their RP is managed up to 5 years. For patients with inactive disease (no recurrence within 3 years), data collection will be retrospective (Figure 2). Up to 500 patients in the US are planned for enrollment at pediatric and adult medical centers, with the potential for expansion to European sites. Additionally, patients will be recruited through a novel, internet-based technology platform and screened for eligibility at a "decentralized" trial site. The registry will include variables obtained from health records, including baseline characteristics and medical history, as well as patient reported outcome (PRO) measures collected every 3 months. The RESONANCE protocol is designed to include a broad population of pediatric and adult patients, regardless of etiology or treatment course, including patients treated with rilonacept. Data will be analyzed to understand disease heterogeneity, variability in treatment and management, and impact on HRQoL. The protocol and Case Report Forms (CRFs) were developed in collaboration with physicians, patients, and patient advocates. Conclusions: Registries utilize real-world data to fill knowledge gaps in the management of less common diseases such as RP. The RESONANCE Registry is the first RP registry designed to collect data across a broad range of patients regardless of treatment. The registry will also serve as a connection point for physicians to further educate and empower patients with information about their disease. In addition, PRO data may enable greater insights into the understanding of the burden of RP from the patient's perspective. Funding Acknowledgement: Type of funding sources: Private company. Main funding source(s): Kiniksa Pharmaceuticals